University governance : Western European comparative perspectives - Paradeise, Catherine (Springer, 2017)
Focuses on 'network-based' governance systems, where coordinating power and control are collectively shared between the major 'social actors or partners' at various levels of the decision-making system. This book tries to use Higher education system to discuss issues on state intervention